Predictive value of early AF recurrence after cryoballoon ablation. (24th May 2021) - Boehmer, AA; Rothe, M; Soether, CM; Abboud, J; Dobre, BC; Kaess, B; Ehrlich, JR
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Early recurrence of atrial fibrillation (ERAF) during a blanking period of 90 days after radiofrequency ablation has been associated with worse long-term outcome. However, the impact of ERAF after cryoballoon pulmonary vein isolation (cryoPVI) is less clear. Objective: A prospective comparison of long-term ablation success after cryoPVI between patients who had ERAF during the blanking period and patients who remained free of AF recurrence during this period. Methods: We analyzed consecutive patients who underwent cryoPVI in a single-center cohort between 2018 and 2020. Follow-up was performed at 3, 6, 12, 18 and 24 months after ablation. Primary endpoints were: symptomatic AF recurrence after a 90-day blanking period for efficacy and bleeding, phrenic nerve injury, stroke or death for safety. Results: 472 consecutive patients with paroxysmal or persistent AF who underwent cryoPVI in a single-center cohort were analyzed. Mean follow-up time was 15 months. 64 patients presented with ERAF during blanking period (age 70 ± 8 years, 52% male gender, CHA2DS2-VASc 2.9 ± 1.5) while 408 patients demonstrated freedom from AF within the first 90 days after cryoPVI (age 69 ± 10 years, 57% male gender, CHA2DS2-VASc 2.7 ± 1.4). At 24 months, Kaplan-Meier estimates showed a significantly higher AF recurrence in patients with ERAF compared to patients without ERAF (74.6 % vs. 33.3%, P < 0.0001, Figure). Cox-regression analysis confirmed ERAF as independent predictor of impaired long-term ablation success after cryoPVI for both paroxysmal and persistent AF (P < 0.0001). Primary safety endpoint occurred in form of pericardial effusion or transient phrenic nerve palsy in one patient with ERAF (1.5%) and five patients without ERAF (1.2%). No deaths or strokes were observed. Conclusion: ERAF during blanking period predicts long-term sucess of patients undergoing cryoPVI. Prospective studies addressing outcome optimisation in this particular cohort of patients are needed.